Excellent Service Training to Improve Communication Competence and Customer Experience in Higher Education: Pelatihan Pelayanan Prima Untuk Tingkatkan Kompetensi Komunikasi dan Customer Experience di Lingkungan Perguruan Tinggi - Rahman, M Arief; Marti Utari; Ferizka Tiara Devani; Fitrianto Puja Kesuma; Nurul Ilma Hasana Kunio (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2026)
This community service activity aimed to improve communication competence and customer experience among service actors in a higher education environment. The training was implemented at Gedung Aula KPA Politeknik Negeri Sriwijaya on 19 February 2026 under the theme of excellent service transformation based on integrity to support the institutional commitment toward an Integrity Zone and Corruption-Free Area. The method consisted of preparation, needs identification, interactive presentation, case-based discussion, service communication simulation, and reflective evaluation. The material emphasized service attitude, active listening, empathy, complaint response, and customer experience touchpoints in academic and administrative services. The activity showed that participants were able to identify the importance of consistent communication behavior, emotional control, and service recovery in creating positive experiences for students, lecturers, partners, and public stakeholders. The implication of this activity is the need for continuous service culture reinforcement through standard operating procedures, role-play-based training, and periodic evaluation of user satisfaction in higher education services.